Conformational Dynamics in Asymmetric Catalysis: Is Catalyst Flexibility a Design Element? - Crawford, Jennifer M.; Sigman, Matthew S. (Synthesis, 2019)
Traditionally, highly selective low molecular weight catalysts have been designed to contain rigidifying structural elements. As a result, many proposed stereochemical models rely on steric repulsion for explaining the observed selectivity. Recently, as is the case for enzymatic systems, it has become apparent that some flexibility can be beneficial for imparting selectivity. Dynamic catalysts can reorganize to maximize attractive non-covalent interactions that stabilize the favored diastereomeric transition state, while minimizing repulsive non-covalent interactions for enhanced selectivity. This short review discusses catalyst conformational dynamics and how these effects have proven beneficial for a variety of catalyst classes, including tropos ligands, cinchona alkaloids, hydrogen-bond donating catalysts, and peptides.1 Introduction2 Tropos Ligands3 Cinchona Alkaloids4 Hydrogen-Bond Donating Catalysts5 Peptide Catalysts6 Conclusion
Keywords: asymmetric catalysis; non-covalent interactions; tropos ligands; organocatalysis; peptide catalysis; conformational dynamics